A Sub-millimeter, Inductively Powered Neural Stimulator - Freeman, Daniel K.; O'Brien, Jonathan M.; Kumar, Parshant; Daniels, Brian; Irion, Reed A.; Shraytah, Louis; Ingersoll, Brett K.; Magyar, Andrew P.; Czarnecki, Andrew; Wheeler, Jesse; Coppeta, Jonathan R.; Abban, Michael P.; et al. (Frontiers in Neuroscience, 2017)
Wireless neural stimulators are being developed to address problems associated with traditional lead-based implants. However, designing wireless stimulators on the sub-millimeter scale (<1 mm3) is challenging. As device size shrinks, it becomes difficult to deliver sufficient wireless power to operate the device. Here, we present a sub-millimeter, inductively powered neural stimulator consisting only of a coil to receive power, a capacitor to tune the resonant frequency of the receiver, and a diode to rectify the radio-frequency signal to produce neural excitation. By replacing any complex receiver circuitry with a simple rectifier, we have reduced the required voltage levels that are needed to operate the device from 0.5 to 1 V (e.g., for CMOS) to 0.25–0.5 V. This reduced voltage allows the use of smaller receive antennas for power, resulting in a device volume of 0.3–0.5 mm3. The device was encapsulated in epoxy, and successfully passed accelerated lifetime tests in 80°C saline for 2 weeks. We demonstrate a basic proof-of-concept using stimulation with tens of microamps of current delivered to the sciatic nerve in rat to produce a motor response.